Ancestralidade e trajetórias evolutivas de ninhos em três famílias de aves: Furnariidae, Troglodytidae e Icteridae - Leite, Abraão de Barros (Universidade Federal de São Carlos, 2024)
Bird nests play important roles in the evolutionary success of this organismal group. For this reason, understanding the origin, evolutionary trajectories and the environmental parameters correlated with nest diversification is important for the understanding of Avian evolution. In this thesis, subdivided into 3 chapters, the nest evolutionary aspects of 3 bird families with distribution mainly concentrated in the New World are addressed. The birds of the family Icteridae build many different nest types, in a variety of habitats, with some species also using old nests from other birds, and others are brood parasitic. In chapter 1, we examined the origin and evolutionary patterns of nest traits and habitat in the Icteridae. We also tested the hypothesis that the use of abandoned nests of other species (non-nest construction) is an intermediate step in the evolution of interspecific brood parasitism, and we addressed the hypothesis that the construction of complex nests is linked to small bodied species. The common ancestor of the Icteridae likely constructed cup-shaped nest, basally supported, and built of leaves/sticks in woodlands. We detected significant evolutionary correlations between nest traits, with nest attachment modes being more often correlated with habitat than nest type and material. We rejected the idea that brood parasitism evolved from non-nest construction, and nest complexity increased with body size, likely due to shifts in nest materials permitting the construction of more resistant nest walls. Birds of the family Trogloditydae build open nests within cavities and enclosed nests on the vegetation, with some a few representatives also constructing enclosed nests within cavities. In chapter 2, we considered open and enclosed as nest types and cavity and vegetation as nest sites. We found that the common ancestor of the Troglodytidae likely constructed enclosed nests within sheltered sites (cavity or crevice), but the radiation of the group was characterized by shifts to exposed nest sites (vegetation) with retention of enclosed nests or retention of sheltered sites with nest simplification (cup nests). Nest site and nest type evolved interdependently, with habitat being poorly correlated with nest evolution. Sheltered nest sites were associated with small body size, likely to avoid competition with other animals for these places. In chapter 3, we used the family Furnariidae to test the hypothesis of nests as key innovations, i.e. the emergence of new traits that can affect transitions to new ecological niches. We addressed the hypothesis of nest type transitions as key innovations for two important proxies of niche diversification, foraging strategy and habitat. We found strong evolutionary correlations between nest type and both foraging strategy and habitat, with model selection and ancestral state reconstructions evidencing nest type shifts preceding niche transitions, confirming the idea of nests as key innovations for the irradiation of this group. This is the first evidence for nest transitions promoting new foraging strategies. These results improved the understanding not only about the evolution of the studied avian families, but also elucidated questions of broad ornithological interest.
Ancestral reconstruction and evolutionary trajectories of nests in three bird families: Furnariidae, Troglodytidae and Icteridae
Keywords: Icteridae; Troglodytidae; Furnariidae; Habitat; Reconstrução ancestral; Correlações evolutivas; Sinal filogenético; Evolução de ninhos; Parasitismo de ninhos; Inovação chave; Ancestral reconstruction; Evolutionary correlations; Nest evolution; Brood parasitic; Key innovation; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA